MENINGKATKAN PEMAHAMAN KEBHINEKAAN GLOBAL MELALUI PENERAPAN METODE MIND MAPPING DI SEKOLAH DASAR - Halimatus Sa'diyah; Ahmad Ipmawan Kharisma; Mochammad Miftachul Huda (Universitas Negeri Medan, 2026)
This research is motivated by the low involvement of students in learning and the lack of innovative methods that facilitate the exploration of ideas and creativity of students. This study aims to determine the activities of teachers and students and to determine the increase in understanding of global diversity of grade V students in learning Pancasila education using the mind mapping method. This research is a Classroom Action Research (PTK) which was carried out in two cycles, with research subjects as many as 9 students. Data collection techniques were carried out through observation, tests (pretest and posttest), and documentation studies. The results showed an increase in teacher and student activities during the learning process, as well as an increase in student learning outcomes in each cycle. In cycle I, learning completeness reached 67% and increased in cycle II to reach the specified success indicator. Thus, the application of mind mapping method can be used as an alternative learning strategy in strengthening the values of global diversity. Keywords: Mind Mapping, Understanding of Global Diversity, Pancasila Education, Elementary school.